PENINGKATAN MOTIVASI BELAJAR IPA SISWA SEKOLAH DASAR MELALUI MODEL PEMBELAJARAN DRAGON BALL: PENELITIAN TINDAKAN KELAS - Nursakinah Nasution; Nurhayati Siregar; Irma Sari Daulay (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2025)
Learning motivation is a crucial factor in the success of science learning at the elementary school level, which requires active engagement, curiosity, and persistence from students. However, science learning in elementary schools often faces the problem of low student motivation due to conventional, teacher-centered instructional approaches with limited interaction. This study aimed to improve the learning motivation of fourth-grade students at SD Negeri 0607 Pagaran Batu through the implementation of the Dragon Ball learning model. This study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were all fourth-grade students. Data on students’ learning motivation were collected through observation and questionnaires based on motivation indicators. The findings indicate a substantial improvement in students’ learning motivation across cycles. In the pre-cycle stage, students’ motivation was predominantly categorized as low, with an average score of 48%. Following the implementation of the Dragon Ball model, motivation increased to 72% in Cycle I and further improved to 82% in Cycle II, exceeding the minimum success criterion of 75%. The results suggest that the Dragon Ball learning model effectively promotes active engagement, cooperative interaction, and intrinsic motivation in elementary science learning. This study contributes to cooperative learning literature by demonstrating the pedagogical value of game-based collaborative strategies in fostering student motivation at the primary education level.